Surface-Imprinted Acrylamide Polymer-Based Reduced Graphene–Gold Sensor in Rapid and Sensitive Electrochemical Determination of αB-Conotoxin - Jia Cao; Jiayue Li; Tianyang Yu; Fei Wang (Sensors)
The quantitative determination of conotoxins has great potential in the development of natural marine peptide pharmaceuticals. Considering the time-consuming sample pretreatment and expensive equipment in MS or LC-MS/MS analysis, an electrochemical sensor combined with molecularly imprinted polymer (MIP) is fabricated for the rapid monitoring of conotoxin αB-VxXXIVA to promote its pharmaceutical value and eliminate the risk of human poisoning. Electrochemically reduced graphene oxide–gold composite (rGO-Au) is modified with chitosan (CS) and glutaraldehyde (GA) to immobilize the macromolecular peptide, conotoxin αB-VxXXIVA. Subsequently, acrylamide (AAM) with a cross-linking agent, N,N′-methylene-bisacrylamide (NNMBA), is introduced into the rGO-Au electrode to form MIPs by electro-polymerization. The proposed MIP-based electrochemical sensor, PAM/αB-CTX/CS-GA/rGO-Au/SPE, exhibits satisfactory sensing performance in the detection of αB-VxXXIVA. Based on current change versus logarithm concentration, a wide linear range from 0.1 to 10,000 ng/mL and a low detection limit (LOD) of 0.014 ng/mL for this sensor are obtained. This work provides a promising method in electrochemical determination combined with MIP for the determination of macromolecular peptides.